Perbedaan efektivitas pasta gigi dengan kandugan bee propolis dan zinc terhadap penurunan tingkat halitosis - Ayu Graha Santi; Desak Nyoman Ari Susanti; Ni Kadek Fiora Rena Pertiwi (Bali Dental Journal, 2018)
Background: Halitosis or bad breath is oral health condition characterized by unpleasant odors emanating consistly from oral cavity. The biggest cause of halitosis is a intraoral condition characterized by increase gram-negative bacteria which produce volatile sulphur compounds (VSCs). There are few ways to reduce halitosis, one of them is using bee propolis and zinc toothpaste. Bee propolis is a substance collected by bees, the most important composition of these compounds is flavonoid. Zinc ions have anti-VSC capable of binding the receptor protein and reduce the sulphur gas production. Objective: This study aimed to know comparison of effectivity tooth paste with bee propolis and zinc. Methods: Experimental method is used in this study, comprised 32 subject divided into 2 group who had criteria for inclusion. Each group was given treatment brushing with bee propolis and zinc toothpaste for 2 minutes. Measurements was done before intervention, after intervention at 0 min, 20 min, 40 min, and 60 min. Results: Collected data was analyzed using the Shapiro-Wilk of normality test and non-parametric Mann-Whitney Test. Based on the test results show that the both toothpaste constant in 20 min. The toothpaste with zinc more effective because zinc have a mean value of 2,0625 in 20 min and was constan in 40 min. Conclusion: The conclusion of this study is toothpaste containing zinc more effective in reducing halitosis compared with toothpaste containing bee propolis.